دور الرقابة الشرعية في ضوء الحوكمة الرشيدة مصباح محمد بن طاهر: The Role of Sharia Supervision In Light of Good Governance - Bentaher, Mesbah Mohamed; Mohd Noh, Mohd Shahid; Mohamad, Mohamad Taqiuddin (Journal Al-Muqaddimah, 2023)
This research aims to identify Sharia supervisory bodies in terms of their concept, tasks, and the mandatory decisions of their decisions, highlight the role of Sharia supervisory bodies in Islamic financial institutions, and study the government and its mechanisms as an entry point for developing the work of Sharia supervisory bodies. This research also derives its importance from the growing interest in both the role of Sharia oversight and the necessity of developing it and the government, and the fact that its foundations, principles, and mechanisms are considered modern concepts at the global level in general, and at the local level in particular, and that awareness of these concepts and their applications leads to achieving a great deal of transparency and justice. Accordingly, this research discusses the problem of applying government tools to the Sharia system within which Islamic financial institutions operate in order to avoid many structural defects that are fundamentally linked to what is known today as the concept of corporate governance. The research follows the descriptive analytical method. The research concluded that it is necessary to provide a guide to the Board of Directors and the Sharia Supervisory Board on how to perform their duties related to Sharia issues, as well as completing the legal framework and raising the efficiency of the Sharia bodies and the supervisory and supervisory bodies of Islamic financial institutions, and working to pay attention to planning, monitoring and evaluating the performance of the Sharia supervisory bodies, as well as disclosure and transparency. About the activity of these bodies, monitoring and evaluating the performance of the Sharia supervisory bodies, as well as disclosure and transparency about the activity of these Sharia bodies to reassure customers, through formulating a framework for the governance of the Sharia supervisory bodies and circulating it to Islamic financial institutions.